Editorial - Jan Nieuwenhuis (Perspectives in Education)
School violence may be defined as any incident in an education institution aimed at interrupting the normal educational project and includes viciousness between learners as well as attacks by learners on school staff and attacks by school staff on learners. It encompasses physical violence, including student-on-student fighting, psychological violence such as verbal abuse, and sexual violence, including rape and sexual harassment. School violence also include various forms of bullying (such as cyberbullying), corporal punishment and carrying weapons to school. School violence has become a widely accepted serious societal problem in recent decades in many countries, especially where weapons such as guns or knives are involved (UNESCO, 2017).